Recent changes in trends of mortality from cervical cancer in Southeastern Brazil - Carolina Terra de Moraes Luizaga; Beatriz Cordeiro Jardim; Victor Wünsch Filho; José Eluf Neto; Gulnar Azevedo e Silva (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To analyze the trends of cervical cancer mortality in Brazilian Southeastern states, and to compare them to Brazil and other regions between 1980 and 2020. METHODS Time series study based on data from the Sistema de Informações de Mortalidade (Brazilian Mortality Information System). Death data were corrected by proportional redistribution of deaths from ill-defined causes and cervical cancer of unspecified portion. Age-standardized and age-specific rates were calculated by screening target (25-39 years; 40-64 years) and non-target (65 years or older) age groups. Annual percentage changes (APC) were estimated by linear regression model with breakpoints. The coverage of Pap Smear exam in the Unified Health System (SUS) was evaluated between 2009 and 2020 according to age group and locality. RESULTS There were increases in corrected mortality rates both in 1980 and in 2020 in all regions, with most evident increments at the beginning of the series. There was a decrease in mortality nationwide between 1980-2020; however, the state of São Paulo showed a discrete upward trend in 2014-2020 (APC=1.237; 95%CI 0.046-2.443). Noteworthy is the trend increment in the 25-39 year-old group in all study localities, being sharper in the Southeast region in 2013-2020 (APC=5.072; 95%CI 3.971-6.185). Screening coverage rates were highest in São Paulo and lowest in Rio de Janeiro, with a consistent decline from 2012 onwards at all ages. CONCLUSIONS São Paulo is the first Brazilian state to show a reversal trend in mortality from cervical cancer. The changes in mortality patterns identified in this study point to the need for reorganization of the current screening program, which should be improved to ensure high coverage, quality, and adequate follow-up of all women with altered test results.